UJI KONSENTRASI AGENS HAYATI Streptomyces sp. TERHADAP PUPA LALAT BUAH Bactrocera sp. - Didin Julia Trisnawati; Wiwik Sri Harijani; Penta Suryaminarsih (Plumula : Berkala Ilmiah Agroteknologi, 2018)
The purpose of this study to determine the concentration of Streptomyces sp. that able to control pupa the fruit fly Bactrocera sp. up to 50 percent of death and the influence of different concentration Streptomyce to long life and symptoms attacks in the fruit flies pupa Bactrocera sp. This research was carried out on June – August 2017 in the health of plants laboratory of Agriculture Faculty UPN “Veteran” Jawa Timur. The research was carried using of randomized block design with the concentration of Streptomyces sp. 5, 10, 15, 20 and 25. Each treatment is repeated as much as five times. The result obtained is an average of a long life the pupa as a result of treatment Streptomyces sp. accelerating to four to six days. Pupae were successfully hatch into imago a physical disability funds have short life. P arasitic symptoms of fruit flies pupa by Streptomyces sp. were changed become black. Postulate Koch of the fruit flies pupa can be seen with the spore and a distinctive smell of Streptomyces sp.